Personal Teacher's View in Building Positive Student Behavior - Jannah, Mulyatul; Fitri; Kenti Lailatul ngaliah; Amanda Wahyuni Anita (International Journal of Education and Teaching Zone, 2023)
This study analyzes the views of teachers in building positive behavior in students in the learning process of students at SMPN 30 Muaro Jambi. This type of research uses descriptive qualitative research so that the data obtained can be seen comprehensively. The subjects of this study were counseling teachers at SMP N 30 Muaro Jambi who were also the sample in this study using total sampling. The data collection technique in this study used interviews with 10 questions about how the guidance counselor views students in building positive behavior. Then analyzed by sorting how to build positive behavior from the largest to the smallest. From the results of this study it is known that the role of the counseling teacher is very important, from the results of the quantitative method we can find out that approximately 10% of students skip classes, 40% of students who lack discipline and 50% of students who play gadgets.